THE DIFFERENCES IN OBESITY RATING BETWEEN BMI AND SKIN FOLD TESTING - Aly, Ezzeldin R. (European Scientific Journal, ESJ, 2014)
Obesity in the United States has grown and is becoming a deadly epidemic. Critics point out that BMI is not useful in the evaluation of health; while convenient; it is not an accurate indicator of true ―obesity.‖ BMI is not a direct measure of body composition, but it is rather an index related to height and weight. To evaluate the validity of body mass index (BMI) 13 college baseball players were used as a sample. We measured their BMI and compared this to their Skin Fold norms. The results showed that all the subjects were classified as overweight when using the BMI equation. On the other hand, the skin fold test results indicated only two baseball players were classified with a risk of obesity. Thus, BMI must be considered with other factors and should not be used as a sole measurement of obesity.